2009
DOI: 10.1103/physrevb.80.045119
|View full text |Cite
|
Sign up to set email alerts
|

Orbital ordering inCa2RuO4investigated byR99

Abstract: The ␥-␥ perturbed angular correlation technique ͑PAC͒ using 99 Ru was applied to investigate the orbital ordering of Ru 4d electrons in Ca 2 RuO 4 . It was confirmed that the ferro-orbital ordering characterized by the double occupation of d xy orbitals at every Ru ion is realized in the stoichiometric Ca 2 RuO 4 . A strong temperature dependence of the quadrupole interaction below the metal-insulator transition around 360 K reflects variation in the occupation of crystal field orbitals enhanced by very pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The Mott insulator Ca 2 RuO 4 [10,11] offers a unique playground to study the non-equilibrium effect on correlated electron systems. In equilibrium, this compound exhibits a firstorder metal-insulator transition at T MI ≃ 360 K [12] and an antiferromagnetic transition at T N = 110 K. The optical conductivity [13], resonant x-ray [14] and perturbed angular correlation [15] experiments have revealed that a ferro-type d xy orbital ordering is realized below T MI , as is expected from flattening of the RuO 6 octahedra at low temperatures [16][17][18][19][20], while different orbital patterns are also suggested [21][22][23]. Recently, Nakamura et al reported that this compound exhibits an electric-field-induced insulator-to-metal transition at E th ∼ 40 V/cm at room temperature [24], which is very low threshold field compared with that for Zener and avalanche breakdown [25].…”
mentioning
confidence: 99%
“…The Mott insulator Ca 2 RuO 4 [10,11] offers a unique playground to study the non-equilibrium effect on correlated electron systems. In equilibrium, this compound exhibits a firstorder metal-insulator transition at T MI ≃ 360 K [12] and an antiferromagnetic transition at T N = 110 K. The optical conductivity [13], resonant x-ray [14] and perturbed angular correlation [15] experiments have revealed that a ferro-type d xy orbital ordering is realized below T MI , as is expected from flattening of the RuO 6 octahedra at low temperatures [16][17][18][19][20], while different orbital patterns are also suggested [21][22][23]. Recently, Nakamura et al reported that this compound exhibits an electric-field-induced insulator-to-metal transition at E th ∼ 40 V/cm at room temperature [24], which is very low threshold field compared with that for Zener and avalanche breakdown [25].…”
mentioning
confidence: 99%
“…22 Perturbed Angular Correlation measurement also suggested two-dimensional character of the magnetic ordering in the parent compound. 48 Spin ordering in similar structures, such as high-T c cuprate La 2 CuO 4 49 and iron-pnictide BaFe 2 As 2 50 , have been demonstrated to arise from two-dimensional spin fluctuations. In the Fe-dope CRO compound, the two phases further undermines each other resulting in two separate transitions.…”
Section: Magnetic Correlations In X=008mentioning
confidence: 99%